Ethnobotany approach taperas of maroon communities of Alcântara, Maranhão, Brasil - Linhares, Jairo Fernando Pereira [UNESP]; Ming, Lin Chau [UNESP]; Pinheiro, Claudio Urbano Bitencourt; Rodrigues, Maria Ivanilde de Araujo [UNESP] (International Society for Phytocosmetic Sciences, 2015)
Alcantara is the second oldest city in the state of Maranhão, which had its splendor even at the time of colonial Brazil, standing out as a major producer of sugar cane and cotton. The agrarian history of the city is old, dating back more than three centuries. Founded in 1648, was an important Maranhão region, besides the production of sugar cane and cotton producing cattle, salt, and food crops, mainly cassava, maize, rice and beans, reaching its best productive time in the mid-nineteenth century. Currently there are about 200 quilombo remaining areas in Alcantara. The objective was to take stock of existing medicinal species in Taperas (areas previously occupied by human presence, and then ruins) of quilombola communities of Manival - coordinates (S 02º 22 '26.6' '; WO 44 29' 27.4 '') and Castelo - coordinates: (S 02º 24 '43.1' '; WO 44 36' 03.07 ''). In the study were interviewed five residents in Manival community and 7 residents of Castelo community to locate Taperas and date the time of abandonment. Taperas were found aged between 30-50 years of neglect. Raised 24 species distributed among 15 families where two species were intentionally introduced for cultivation and at one point abandoned as cultivated species: as cotton (Gossypium arboreum L. - Malvaceae) and mango (Mangifera indica L. - Anacardiaceae). The most representative botanical families were Euphorbiaceae (16.66%), Arecaceae, Fabaceae and Malvaceae with 8.33% each. The leaf is 50% utilization of the plant parts. The medicinal uses are varied to control lice and fleas, treat kidney problems, blood cleanser, general pain, and even for treatment of gastritis.
Keywords: Medicinal plants; Ruderal; Secondary vegetation